Risk, return gap, and investment choice of Vietnamese firms: Impacts from global uncertainty and monetary policy - To Cong Nguyen, Bao; Nguyen Khac Quoc, Bao; Bui Thi Thao, Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study develops and tests an investment choice model based on the risk and return gap of investment forms under the lens of global uncertainty and monetary policy. Using panel data from non-financial firms listed in Vietnam for the period 2013‒2021, we find that the risks of investing in fixed assets and global economic policy uncertainty increase, causing firms to invest more in financial assets, which can be considered a profitable and highly liquid haven. Monetary policy can help combat the phenomenon of financialization; however, in the context of global uncertainty, the role of monetary policy is diminished. Additionally, there is no evidence that the return gap between investments in fixed assets and financial assets affects the financial investment choice behavior of firms.
Keywords: Global uncertainty; Monetary policy; Investment choice; Vietnam